Promoting gender - Equitable agricultural value chains: The role of corporate social responsibility in Nigeria's Niger Delta - Joseph I. Uduji; Elda N. Okolo-Obasi (African Governance and Development Institute (AGDI), 2022)
Purpose - The purpose of this paper is to critically examine the multinational oil companies' corporate social responsibility (CSR) initiatives in Nigeria. Its special focus is to investigate the impact of the global memorandum of understanding (GMoU) on promoting genderequitable agricultural value chains in the Niger Delta region. Design/ methodology/approach - This paper adopts a quasi-experimental design that used survey research technique, aimed at gathering information from a representative sample of the population, as it is essentially cross-sectional, describing and interpreting the current situation. A total of 760 rural women (380 from the treatment group and another 380 from the control group) were sampled across the Niger Delta region. Findings - The results from the use of a combination of a logit model and propensity score matching indicate a significant relationship between GMoU model and gender-equitable agricultural value chains in the Niger Delta, Nigeria. Practical implications - This implies that CSR of a multinational oil companies is a critical factor in the need to integrating gender into agricultural value chains, and achieving the goal of increasing agricultural growth and expanding the stable food supply. Social implications - It suggests that creating and sustaining competitive and equitablyoriented value chains that help small-scale farmers, especially women will require examining gender issues and proactively integrating gender components into GMoU policies and action plans of MOCs for value chain analysis and development strategies in the Niger Delta. Originality/value - This research contributes to gender debate in agricultural value chains from a CSR perspective in developing countries and rationale for demands for social projects by host communities. It concludes that business has an obligation to help in solving problems of public concern.
Keywords: 330; Gender; Agriculture; Value chains; Corporate social responsibility; Multinational oil companies; sub-Saharan Africa